Prolotherapy is not superior to control or placebo-based conservative treatments for rotator cuff tendinopathy: a systematic review and meta-analysis - Thamrongskulsiri, Napatpong; Vitoonpong, Timporn; Itthipanichpong, Thun; Limskul, Danaithep; Tanpowpong, Thanathep; Kuptniratsaikul, Somsak (Clinics in shoulder and elbow, 2025)
This systematic review and meta-analysis aimed to assess the efficacy of prolotherapy compared to control or placebo-based treatments. A comprehensive search of PubMed, Ovid, and Scopus was conducted up to April 2025. Inclusion criteria encompassed clinical studies comparing prolotherapy with control or placebo treatments and evaluating outcomes such as pain, function, and range of motion. Eight studies involving 431 participants met the inclusion criteria. Patient-reported outcomes, including pain visual analog scale and Shoulder Pain and Disability Index, showed no statistically significant differences between prolotherapy and controls. Prolotherapy demonstrated a small but statistically significant improvement in shoulder abduction (mean difference, 7.08°; 95% CI, 2.49°-11.66°). Other range of motion measures, such as forward flexion, internal rotation, and external rotation, showed no significant differences. Radiographic outcomes, including tendon thickness and elasticity, suggested potential structural benefits but did not consistently translate to clinical improvements. Prolotherapy is not superior to control treatments for rotator cuff tendinopathy. While it offers minor gains in shoulder abduction, its clinical benefits are limited. Level of evidence: III.